Targeted live-cell nuclear delivery of the DNA 'light-switching' Ru(II) complex via ion-pairing with chlorophenolate counter-anions: the critical role of binding stability and lipophilicity of the ion-pairing complexes. Issue 20 (4th October 2019) - Chao, Xi-Juan; Tang, Miao; Huang, Rong; Huang, Chun-Hua; Shao, Jie; Yan, Zhu-Ying; Zhu, Ben-Zhan
Abstract: We have found recently that nuclear uptake of the cell-impermeable DNA light-switching Ru(II)-polypyridyl cationic complexes such as [Ru(bpy)2 (dppz)]Cl2 was remarkably enhanced by pentachlorophenol (PCP), by forming ion-pairing complexes via a passive diffusion mechanism. However, it is not clear whether the enhanced nuclear uptake of [Ru(bpy)2 (dppz)] 2+ is only limited to PCP, or it is a general phenomenon for other highly chlorinated phenols (HCPs); and if so, what are the major physicochemical factors in determining nuclear uptake? Here, we found that the nuclear uptake of [Ru(bpy)2 (dppz)] 2+ can also be facilitated by other two groups of HCPs including three tetrachlorophenol (TeCP) and six trichlorophenol (TCP) isomers. Interestingly and unexpectedly, 2, 3, 4, 5-TeCP was found to be the most effective one for nuclear delivery of [Ru(bpy)2 (dppz)] 2+, which is even better than the most-highly chlorinated PCP, and much better than its two other TeCP isomers. Further studies showed that the nuclear uptake of [Ru(bpy)2 (dppz)] 2+ was positively correlated with the binding stability, but to our surprise, inversely correlated with the lipophilicity of the ion-pairing complexes formed between [Ru(bpy)2 (dppz)]Cl2 and HCPs. These findings should provide new perspectives for future investigations on using ion-pairing as an effective method for delivering other bio-active metal complexes into their intended cellular targets.